Effects of megasphaera elsdenii on ruminal pH, ruminal concentrations of organic acids, and bacterial genomes following a grain challenge - McDaniel, M.R.; Higgins, James J.; Heidenreich, J.M.; Shelor, M.K.; Parsons, G.L.; Henning, P.H.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Upon arrival in feedlots, cattle normally must be adapted to high-concentrate diets. The microbial population in the rumen of incoming cattle normally is suited to digestion of forages, and when cattle are transitioned onto concentrate diets, opportunistic bacteria that produce lactic acid can proliferate rapidly, leading to excesses of lactic acid in the rumen. High levels of lactic acid in the rumen may cause mild to severe acidosis. Megasphaera elsdenii is a lactate-utilizing bacterium that normally is present in rumens of cattle that have been adapted to high-grain diets, but numbers of the organism are relatively low during the step-up phase. Increasing the numbers of lactate-utilizing bacteria in newly arrived cattle by orally dosing with M. elsdenii may be a useful means of reducing the risk of ruminal acidosis in feedlot cattle. Our objectives were to evaluate ruminal parameters and determine efficacy of increasing ruminal populations of lactateutilizing bacteria in cattle following an abrupt diet change and administration of 10 mL (low dose), 100 mL (medium dose), or 1000 mL (high dose) of a culture containing 1.62 × 108 CFU/mL of live M. elsdenii compared with a control group given a placebo without live Megasphaera.
Keywords: Beef; Cattle; Megasphaera elsdenii